Korral Kool systems in desert environments - Ortiz de Janon, Xavier Alejandro (Kansas State University, 2009)
A series of experiments was developed to investigate how Korral Kool® (KK) systems work in arid climates to prevent heat stress on dairy cows. These experiments were conducted during summer on a commercial dairy farm in eastern Saudi Arabia. In the first experiment, the core body temperatures (CBT) of 63 multiparous cows were evaluated when KK were operated for 18, 21 and 24h/d. Animals were housed in 9 different pens, which were randomly assigned to treatment sequence in a 3x3 Latin square design. In the second experiment, 21 multiparous and 21 primiparous cows were housed in 6 different pens, which were randomly assigned to sequence of treatments (KK operated for 21 or 24h/d) in a switchback design. In the third experiment, 7 primiparous and 6 multiparous lactating cows were assigned to one of two pens, which were randomly assigned to treatment sequence in a switchback design. Treatments in the third experiment were KK used with or without feedline soakers 24h/d. In the fourth experiment, 20 multiparous cows were randomly assigned to one of two pens, which were randomly assigned to treatment sequence in a switchback design. Treatments in this experiment were KK operated for 24h/d while feedline soakers were operated for 12h/d. In the fifth experiment, 2 different sizes of KK were compared (BIG and SMALL); 48 multiparous cows were randomly assigned to 8 pens and pens were randomly assigned to sequence of treatments (KK were operated for 21 or 24h/d) in a switchback design. Results demonstrated that for multiparous cows in desert climate conditions, it is advisable to operate KK systems continuously regardless of the size of KK system used, whereas KK operating time could potentially be reduced from 24 to 21h for primiparous cows. Reducing operation time should be done carefully, however, because CBT was elevated in all treatments. Feedline soakers complementing KK systems decreased the CBT of dairy cows housed in desert environments. However, the combined systems were not adequate to lower CBT to normal temperatures in this extreme environment.
Keywords: Korral Kool; Heat stress; Dairy cows; Agriculture, Animal Culture and Nutrition (0475)